A Copper Metal–Organic Hydrogel as a Catalyst for SO2 and CO2 Fixation under Ambient Conditions. Issue 31 (12th August 2019) - Karan, Chandane Kumar; Bhattacharjee, Manish
Abstract : A copper metal–organic hydrogel (MOG) has been synthesized using an amino acid‐based ligand, Na2 HL H3 L = 2‐(3, 5‐di‐ tert ‐butyl‐2‐hydroxybenzyl)amino succinic acid as a gelator. The metallohydrogel exhibits pH‐responsive nature as well as chemical responsiveness. Besides, it shows rapid thixotropic behavior when external mechanical forces are applied. The metal–organic hydrogel can be used as a heterogeneous catalyst for the reaction of SO2 and CO2 with epoxides to produce cyclic 1, 3, 2‐dioxathiolane‐2‐oxides and carbonates, respectively. The conversions were found to be dependent on the size and type of the side chain of the epoxides. Abstract : A copper(II) hydrogel has been synthesized and characterized. The xerogel can be used as a heterogeneous catalyst for the conversion of SO2 1, 3, 2‐dioxathiolane‐2‐oxides with high diastereoselectivity. The xerogel can also be used for the chemical fixation of CO2 .,